Uwagi w sprawie publicznoprawnej determinacji ram przedmiotowych publicznego prawa gospodarczego - Małecki, Witold (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The evolution of administrative economic law into public economic law should cause extension of the scope of this section of law, corresponding to its name containing two determinants. However, the scope of public economic law presented in contemporary Polish comprehensive manuals of public economic law does not contain any references to economic criminal law, which is undoubtedly a section of law situated within the confines of public law. In order to determine the meaning of the determinant “public” in the name “public economic law” two models were proposed. In a “shaping” model the determinant “public”, together with the determinant “economic”, defines the scope of public economic law. Only accepting the view on economic law as an independent branch of law and — consequently — the view on public economic law as a divisive factor of the economic law as an independent branch of law allows to justify an omission of economic criminal law provisions which should be included into criminal law. Regarding economic law as an independent branch of law does not entitle one to include such provisions into it if they are classified as a part of another independent branch of law — in this case: criminal law. Another model is a “descriptive” one, in which the determinant “public” does not define the scope of public economic law — the scope is determined by the definition of public economic law. The only role of the determinant “public” is to describe a category of provisions that are included in public economic law. The model, however, does not justify the omission of economic criminal law provisions in the manuals because of a broad shape of the definition of public economic law presented in Polish literature.
Keywords: publiczne prawo gospodarcze; prawo gospodarcze; prawo publiczne; prawo karne gospodarcze; gałąź prawa